Endovascular Repair of a Post-Renal Transplant Internal Iliac Artery Pseudoaneurysm. (August 2021) - Vijayvergiya, Rajesh; Kasinadhuni, Ganesh; Sharma, Ashish; Lal, Anupam
Anastomotic site pseudoaneurysm following renal transplantation is a rare vascular complication. Its etiology include defective suture techniques and infections. The clinical presentation includes allograft dysfunction, local mass effect, exsanguination, and rupture. Open surgical repair is associated with significant morbidity and allograft dysfunction. Endovascular stent-graft can be a less invasive, alternative approach. We describe a case of large pseudoaneurysm arising from the internal iliac artery in a post-renal transplant patient. It was successfully treated with the stent-graft. The externally compressed right common iliac vein was also treated with a self-expanding non-graft stent. Thus, endovascular approach can be an effective alternative to open repair for post-renal transplant iliac artery pseudoaneurysm.